2011
DOI: 10.1007/s00246-011-9961-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of ECMO Support in Infants with Tachycardia-Induced Cardiomyopathy

Abstract: The development of tachycardia-induced cardiomyopathy (TIC) is related to the rate and duration of supraventricular tachycardia (SVT). Infants may be more susceptible to TIC because early symptoms might be unrecognized. Extracorporeal membrane oxygenation (ECMO) may improve outcome in patients with SVT and TIC; however, clinical predictors of infants who require ECMO support have not been determined. The purpose of this study was to identify predictors of the need for ECMO in infants with SVT and TIC. Sixteen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
0
2
Order By: Relevance
“…[33][34][35] The life history of ectopic atrial tachycardia includes possible progression to congestive cardiac failure and it features as a reversible cause of cardiomyopathy. [33][34][35][36][37] EAT and permanent junctional reciprocating tachycardia constitute a minor proportion of SVTs, but they are a major cause of Tachycardia Induced Cardiomyopathy (TIC) seem in infants and children less than 5 years old. 38 The cardiomyopathy results from the erratic nature of these tachycardias in most of the patients.…”
Section: 20mentioning
confidence: 99%
“…[33][34][35] The life history of ectopic atrial tachycardia includes possible progression to congestive cardiac failure and it features as a reversible cause of cardiomyopathy. [33][34][35][36][37] EAT and permanent junctional reciprocating tachycardia constitute a minor proportion of SVTs, but they are a major cause of Tachycardia Induced Cardiomyopathy (TIC) seem in infants and children less than 5 years old. 38 The cardiomyopathy results from the erratic nature of these tachycardias in most of the patients.…”
Section: 20mentioning
confidence: 99%
“…The first phase from 2011 to 2013 was the initial exploration of ECMO, and researchers mostly attached attentions on the initial exploration of ECMO's treatment of children suffering from severe cardiopulmonary diseases and patients with influenza A (H1N1) (15)(16)(17)(18)(19). At the beginning of the first phase, many scholars found that ECMO was irreplaceable in the treatment of severe respiratory failure in children with severe illnesses, especially newborns and infants (20,21). However, with the outbreak of H1N1 in 2013, ECMO has become the focus of research, owing to the high fatality rate and the numerous complications such as explosive acute lung injury (ALI) and acute respiratory distress syndrome (9ARDS) (22).…”
Section: Research Hotspots Change Greatly Over Timementioning
confidence: 99%
“…In general, survival is better in these patients (62% cardiomyopathy; 70% myocarditis) than in those with structural congenital etiologies of heart failure because in many cases, the underlying disease process is self-limited or manageable with appropriate pharmacotherapy. Additional causes of pediatric heart failure that may require ECLS include refractory or chronic dysrhythmia, infection, and myocardial infarction ( 18 , 19 ).…”
Section: Bridge To Transplantmentioning
confidence: 99%